2019
DOI: 10.21125/iceri.2019.0675
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Inclusive Group Work

Abstract: Group and team work promote key employability skills, required by many degree accrediting bodies, and are viewed as active and authentic ways of learning, supporting the construction of knowledge among peers. However, managing expectations, group dynamics, and assessing group and individual contributions is challenging. Group work approaches that consider diversity and promote equitable participation by all students, enhance the culture of the learning environment and are more likely to lead to productive grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These barriers are explored in more depth in a different publication (Lister et al, 2021), but the examples given in this paper do support the broader literature in this area. For example, the barrier presented by the 'Cognitive load of studying when in low mental health' aligns with Weller et al's findings about students withdrawing from study due to feeling 'overwhelmed' by curriculum content (Weller et al, 2018); studies have linked distressing curriculum content with mental health challenges for students (Bentley, 2017;Slavin et al, 2014); 'anxiety around groupwork' is a theme in the literature (McPherson et al, 2019), and there are many studies aiming to understand or alleviate stress around exams or assessment (Jones et al, 2020). This supports research contentions that triggers for mental health difficulties can reside within higher education environments, systems and curricula as well as within the individual (Lister et al, 2021;Markoulakis & Kirsh, 2013;Tinklin et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…These barriers are explored in more depth in a different publication (Lister et al, 2021), but the examples given in this paper do support the broader literature in this area. For example, the barrier presented by the 'Cognitive load of studying when in low mental health' aligns with Weller et al's findings about students withdrawing from study due to feeling 'overwhelmed' by curriculum content (Weller et al, 2018); studies have linked distressing curriculum content with mental health challenges for students (Bentley, 2017;Slavin et al, 2014); 'anxiety around groupwork' is a theme in the literature (McPherson et al, 2019), and there are many studies aiming to understand or alleviate stress around exams or assessment (Jones et al, 2020). This supports research contentions that triggers for mental health difficulties can reside within higher education environments, systems and curricula as well as within the individual (Lister et al, 2021;Markoulakis & Kirsh, 2013;Tinklin et al, 2005).…”
Section: Discussionmentioning
confidence: 65%
“…Such activities tend to push students out of their comfort zone and are also associated with higher rates of success . However, research shows that these collaborative activities are associated with higher levels of student anxiety (McPherson et al, 2019). Thorpe (2008, p. 59) also notes that students tend only to engage with collaborative activities which are linked to assessment, and stresses it is crucial to make the process "enjoyable as well as mandatory" to maximize effective engagement.…”
Section: Designing For Inclusionmentioning
confidence: 99%
“…Baik et al also found that assessment design impacted on wellbeing, with student perceptions of clarity and fairness in design being particularly critical (2019), while Hill et al highlight impacts of assessment feedback on student wellbeing (2021). Specific assessment activities, such as groupwork, can be a barrier for wellbeing ( McPherson et al, 2019 ), while impacts of power dynamics involved in faculty-centred as opposed to student-centred pedagogies have been found to affect students’ confidence and wellbeing ( Felton and Stickley, 2004 ; Hill et al, 2019 ). Feeling ‘overwhelmed’ has been linked to student withdrawal ( Weller et al, 2018 , p: 43), and, of course, failure and fear of failure are also major contributors to student academic stress or distress ( Whittle et al, 2020 ).…”
Section: Background and Literaturementioning
confidence: 99%
“…For example, Tinklin et al identified ‘Lack of understanding among lecturers’ and ‘badly designed learning experiences’ as barriers (2005, p: 510), and Baik et al found that lack of clarity in teaching materials, low levels of classroom interaction and lack of variety in activities impacted negatively on wellbeing (2019). Specific activities, such as groupwork, can be a barrier for wellbeing ( McPherson et al, 2019 ), while impacts of power dynamics involved in faculty-centred as opposed to student-centred pedagogies have been found to affect students’ confidence and wellbeing ( Felton and Stickley, 2004 ; Hill et al, 2019 ). Feeling ‘overwhelmed’ by curriculum content has been linked to student withdrawal ( Weller et al, 2018 , p: 43), and distressing curriculum content has been shown to present particular mental health challenges for some students ( Slavin et al, 2014 ; Bentley, 2017 ).…”
Section: Background and Literaturementioning
confidence: 99%
“…For example, Tinklin et al (2005) identified "Lack of understanding among lecturers" and "badly designed learning experiences" as barriers (p. 510), and Baik et al (2019) found that lack of clarity in teaching materials, low levels of classroom interaction and lack of variety in activities impacted negatively on wellbeing. Specific activities, such as groupwork, can be a barrier for wellbeing (McPherson et al, 2019), while impacts of power dynamics involved in faculty-centered as opposed to student-centered pedagogies have been found to affect students' confidence and wellbeing (Felton and Stickley, 2004;Hill et al, 2019). Feeling "overwhelmed" by curriculum content has been linked to student withdrawal (Weller et al, 2018, p. 43), and distressing curriculum content has been shown to present particular mental health challenges for some students (Slavin et al, 2014;Bentley, 2017).…”
Section: Student Mental Health and Wellbeing In Higher Educationmentioning
confidence: 99%